The effect of wheat and barley type and method of exposure in response khabra beetle to microwave radiation: THE EFFECT OF WHEAT AND BARLEY TYPE AND METHOD OF EXPOSURE IN RESPONSE KHABRA BEETLE TO MICROWAVE RADIATION - AL-Ebady, Emad Qaseem; AL-Barwary, Mohammad Ablrahman Sdeek (Journal of Kerbala for Agricultural Sciences, 2018)
The results of the study effect of host food type hard wheat (Smito) , soft wheat (Tamoz 2) , white barley and local black barley with two application method of exposure ( insect without food and insect with food) to microwave power at 200, 500 and 800 watt at 15, 30, 45, 60 and 90 second as exposure period on the grain beetle ( Khabra) T. granarium . The results showed that the killing percentage the Khabra beetle adults , was increased by increasing of microwave level and exposure period when reared on four type of host food for insect without food 53.49 , 43.99 , 27.99% of microwave level and 21.94 , 30.27 , 38.61 , 51.39 and 66.94% for exposure period . The results also showed that the mortality of Khabra adults with food was 21,49 , 61.16 and 72.16% for microwave level and 31.11 , 34.16 , 58 , 64.72 and 69.44% for exposure period respectively .The results also showed that the mortality of Khabra adults to the microwave irradiation with the host food was significantly higher than their mortality when exposured to the microwave irradiation without host food as 51.60 and 41.83% . The results showed that the lethal dose value for adults mixed without host food ranged between 503-892 watt at 51-102 second , while, the lethal dose value of adults with food ranged between 340-442 watt at 29-41 second .